Estimation of the engine performance and emission characteristics of hydrogen feed vehicles with modified injection fuel system. (1st December 2022) - Wu, Yingji; Devi, P. Booma; Anbarasu, A.; Sołowski, Gaweł; Chanh, Huynh Cong; Chi, Nguyen Thuy Lan; Nasif, Omaima; Alharbi, Sulaiman Ali; Xia, Changlei
Graphical abstract: Highlights: The diesel engine is tested with the hydrogen blends with various fractions of diesel. A series of test was conducted in an four-stroke, multi-cylinder diesel engine with the hydrogen blends. Addition of the hydrogen increased the Brake thermal efficiency by reducing fuel consumption. The emissions of the NOx and HC were dropped significantly as the concentration of the hydrogen in the diesel was increased. Abstract: Hydrogen as the secondary fuel in the existing diesel engines may improvise the performance and emission characteristics. Significant research has been conducted recently on hydrogen as the auxiliary fuel. In this current study, the diesel engine is tested with the hydrogen blends. The hydrogen is mixed with the diesel in the fractions of 10%, 20% and 30%, tested by varying the engine speeds and engine loads. Trail runs were made on the multicylinder water-cooled diesel engine to determine the brake thermal efficiency and the brake specific fuel consumption. In addition to the above, the emissions of pollutants such as NOx, HC and CO were also determined. The results releveled that addition of the hydrogen amplified the performance of the engine by reporting superior BTE and reduced fuel consumptions rates. Further, the emissions of the NOx and HC were dropped significantly as the concentration of the hydrogen in the diesel was increased. Based on the recorded value 30% hydrogen blends reported the maximum BP and BTE of 7.65 kW and 49.2%. With regard to the emissions compared to diesel, hydrogen addition reduces the NOx by 2.8%, 4.5% and 15% for the H10, H20 and H30 respectively. Based on the series of evidence it is evident that hydrogen addition to the CI engine can be the substantial substitute for fossil fuels.